Financialization and its discontents - Perry Mehrling (Finance and Society, 2017)
Finance is not something separate from society. It is neither a Marxian superstructure nor a monetarist veil, but rather the very substance of modern social relations, a web of time-dated promises to pay that stretches from now into the future, and from here around the globe. Financial relationships are not about mediating something else on the "real" side of the economy; they are the constitutive relationships of the whole system. Financial globalization and global financialization have produced a global Financial Society, hierarchical and inherently unstable. The problem confronting social analysts is not so much to find the social in the money grid - the money grid is already social - but rather to understand the dynamical operations of that grid on its own terms. This essay sketches the fundamental processes that produce and reproduce Financial Society - settlement and market-making - as an attempt to provide a realistic point of departure for any feasible project of reform.
Keywords: 300; Financialization; Polanyi; Minsky; survival constraint; market theory of money